Pengaruh Inflasi Terhadap Tingkat Pengangguran Di Kota Bima - Putri Rahmania; Puji Muniary; M. Rimawan (Universitas 45 Surabaya, 2023)
The existence of inflation at the same time as unemployment has become a problem in an economy. Inflation is almost unavoidable for a system that has exceeded its peak production capacity. Inflation has an important role in changes in the number of unemployed. (Andiny, Desrini Ningsih, 2018) The higher the inflation rate itself, the higher the level of fulfillment of needs can result in the emergence of poverty among the community which is caused by the higher prices of goods and services and the inflation rate in Indonesia which is capable of fluctuating from year to year. According to (Putong, 2017) inflation is calculated based on index numbers collected from several types of goods bought and sold on the market at each level of economic growth (these goods are of course the most numerous and are the basic needs of society). Based on the economic growth data, an index number is compiled. The index number that takes into account all goods purchased by consumers during each economic growth is called the Consumer Economic Growth (HK) index. According to (Sukirno, 2016) inflation increases suddenly or occurs as a result of a certain event that occurs in outside the government's expectations, for example the effect of calculating the value of money which is very large or political instability. Factors that influence the level of inflation on unemployment in Bima City are because the higher inflation that occurs can result in decreased economic growth, so that there will be an increase in the number of unemployed